2013
DOI: 10.1103/physreve.87.012703
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative dynamics of microtubule ensembles: Polymerization forces and rescue-induced oscillations

Abstract: We investigate the cooperative dynamics of an ensemble of N microtubules growing against an elastic barrier. Microtubules undergo so-called catastrophes, which are abrupt stochastic transitions from a growing to a shrinking state, and rescues, which are transitions back to the growing state. Microtubules can exert pushing or polymerization forces on an obstacle, such as an elastic barrier if the growing end is in contact with the obstacle. We use dynamical mean-field theory and stochastic simulations to analyz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 29 publications
(109 reference statements)
1
40
0
Order By: Relevance
“…Another model proposes that oscillations occur via a general mechanobiochemical feedback (25). Models of force-dependent MTs interacting with the same object also exhibit cooperative behavior (5,(26)(27)(28)(29). However, these models do not explain error correction dynamics.…”
mentioning
confidence: 99%
“…Another model proposes that oscillations occur via a general mechanobiochemical feedback (25). Models of force-dependent MTs interacting with the same object also exhibit cooperative behavior (5,(26)(27)(28)(29). However, these models do not explain error correction dynamics.…”
mentioning
confidence: 99%
“…These approaches include details of the hydrolysis mechanism into the model for the catastrophe rate [21,22,23,24]. One focus of these approaches was the explanation of the behavior of MT growth dynamics under force.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these theoretical studies have demonstrated that the stall force of multiple, non-interacting filaments without ATP/GTP dynamics, scales linearly with the number of filaments [26,[28][29][30]54]. In contrast, a few other recent papers quite clearly report that inclusion of ATP/GTP hydrolysis can lead to either enhanced or reduced cooperativity in the maximum force generated by multiple growing filaments; the stall forces need not always scale with the number of filaments [31,[56][57][58].…”
Section: Introductionmentioning
confidence: 91%
“…On the theoretical and computational front, there are a number of very detailed models for understanding the force-velocity dynamics of a single biofilament [50][51][52][53], as well as a few that try to model the dynamics of multiple biofilaments [26,[28][29][30][31][54][55][56]. Some of these theoretical studies have demonstrated that the stall force of multiple, non-interacting filaments without ATP/GTP dynamics, scales linearly with the number of filaments [26,[28][29][30]54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation